THE RELATIONSHIP BETWEEN COGNITIVE IMPAIRMENT AND THE LEVEL OF BDNF IN YOUNG PEOPLE - Белоусова, Надежда Павловна; Громова, Ольга Алексеевна; Пепеляев, Евгений Геннадьевич; Субботин, Анатолий Васильевич; Семенов, Владимир Александрович (Medicine in Kuzbass, 2017)
The relevance of the study is due to interest in the problem of cognitive deficits, actively developed in the modern scientific literature. At the same time, the mechanisms of the development of cognitive deficiency remain insufficiently studied.The aim of the study is to study the quantitative content of the cerebral neurotrophic factor of human blood serum (BDNF) and its effect on cognitive function in young people.The material of the study was the results of psychological testing of two groups of persons (19-27 years and 41-60 years), data on the level of BDNF in the sera of the interviewed. We used: questionnaire «quality of life – neurological module», BDI scale, AR technique. Luria «10 words», the «Schulte table» technique, a technique for studying visual-spatial gnosis. To determine the level of BDNF, the ELISA method was used.As a result of the study, the average BDNF level was exceeded by more than 20 % in young people compared with representatives of the middle-aged group. In young people, the decline in cognitive functions correlates with an increase in the level of BDNF, which, on the one hand, can be explained both by higher regenerative abilities of the young organism and as a prerequisite for explaining the pathogenetic aspects of the initial manifestations of cognitive deficits.
Keywords: cognitive deficits; neurotrophins; BDNF; dementia; Schulte tests